The Role and Importance of Local Economic Development in Urban Development: A Case of Harare - Gladys Mandisvika (Centre for Behaviour and Wellness Advocacy, 2015)
The study assessed the role and importance of Local Economic Development as a means of enhancing urban development paying particular attention to the regulators of Local Economic Development in Harare. Local Economic Development is a process which encourages partners from the community, public sector, private sector and non-governmental sectors to work collectively to create better conditions for economic growth and employment generation with the aim of improving the locality economic future and the quality of life for all citizens. The study was premised on the theory of competitive advantage which puts up that prosperity and wealth creation is determined by microeconomic factors and that prosperity means increasing the standards of living for the local people and ultimately their quality of life. Primary data for the research was gathered through observation and key informant interviews. Data on key stakeholders understanding on the concept of Local Economic Development, how it is being practised and how the current regulatory framework enhance or impinge on local people's participation in Local Economic Development was collected. Secondary data was also collected from Harare's 2014 budget, census and existing forward plans. The study revealed that the practice of Local Economic Development in Harare is biased towards the setting aside of land zoned for industrial and commercial uses and implementation of development control parameters. Small to Medium Enterprises and the informal sector have also been identified as the major forms of Local Economic Development that citizens are involved in. However, the study revealed that proper policy frameworks which guide practice of Local Economic Development initiatives were missing